Effects of earthworms and arbuscular mycorrhizal fungi on improvement of fertility and microbial communities of soils heavily polluted by cadmium. (January 2022) - Wang, Gen; Wang, Li; Ma, Fang
Abstract: Soil bacterial community (SBC) and fertility are pivotal for the evaluation of phytoremediation performance. Although affected by earthworms (E) and arbuscular mycorrhizal fungi (AMF), little is known about the impacts of the E-AMF interaction on the variation of SBC and fertility in cadmium (Cd)-spiked soil. We elucidated these impacts in rhizosphere soil of Solanum nigrum L. Loss of nutrient availability, and SBC diversity was observed in Cd-polluted soil. AMF increased available phosphorous (AP), whereas E increased available potassium (AK). In soils with 60 and 120 mg/kg Cd, the contents of AK, AP, and soil organic matter (SOM) increased by 7.0–19.7%, 23.7–25.5%, and 11.5–17.4%, respectively; and the residual Cd after remediation decreased by 7.9–8.5% in soils treated with EAM compared to untreated soil. EAM-treated soil had higher alpha diversity estimators compared to uninoculated soil. The predominant bacterial phyla were Proteobacteria and Bacteroidetes, accounting for 72.5–84.0%. Redundancy analysis showed that total carbon (TC), SOM, pH, and C/N ratio were key factors determining SBC at the phylum level, explaining 26.9, 24.1, 15.1, and 14.8% of the total variance, respectively. These results suggested that EAM affected SBC composition by altering SOM, TC, and C/N ratio. The E-AMF cooperation ameliorates soil nutrients, SBC diversity, and composition, facilitating phytoextraction processes. Graphical abstract: Image 1 Highlights: Earthworm and AMF supply different nutrients for S. nigrum. Proteobacteria and Bacteroidetes are enriched due to strong resistence to Cd. Soil pH and C/N ratio can drive bacterial community composition and diversity. Earthworm-AMF-hyperaccumulator cooperation facilitates resurgence of soil health.